Implementing the Management of Character Education in SDIT Nurul Ishlah Banda Aceh - Yasin, Nurhayati; Yusrizal, Yusrizal; Niswanto, Niswanto (FKIP Universitas Lampung, 2021)
The purpose of this research is to know the character education program, program implementation, evaluation program and the obstacles that are found in SDIT Nurul Ishlah Banda Aceh in implementing character education. Research subject of the principal, the chairman of the foundation, the class and parents. Data collection techniques through interviews, observations, and documentation studies. Research result showed that character education program at SDIT Nurul Ishlah is good enough, compiled before the school year begins. The implementation of character education follows a national curriculum combined with SDIT Nurul Ishlah curriculum. The teacher council prepares syllabus and lesson plan with character values, teachers can add praiseworthy traits of morality such as Siddig, Tabligh, Fatanah and Amanah. The evaluation of character education is conducted periodically and comprehensively at the end of semester, with the aim to know the aspects that need to be continuously improved. Keywords: management, character education, national curriculum. DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202129